A meta‐analytic review of attitudes towards the sexuality of adults with intellectual disabilities as measured by the ASQ‐ID and related variables: Is context the key?. Issue 10 (15th August 2022) - Correa, A. B.; Moreno, J. D.; Castro, A.
Abstract: Background: The attitudes of others towards the sexuality of people with intellectual disabilities are one of the main perceived barriers to them expressing their sexuality. Research on what influences these attitudes yields heterogeneous results. Method: A systematic review of the literature and a meta‐analysis were carried out. Results: Eleven studies using the Attitudes to Sexuality Questionnaire—Individuals with an Intellectual Disability (ASQ‐ID) were included. Within the included studies, the country's socio‐economic development and level of individualism were associated with attitudes towards the sexual rights, parenting and self‐control of adults with intellectual disabilities. General population and staff samples held more favourable attitudes than family samples in terms of sexual rights and parenting. Age and gender did not yield significant results. Conclusions: Variables related to country context may underlie the differences observed between countries and therefore influence the population's general thinking and ideologies. Unexpectedly, no age differences were observed. Gender‐related results may reflect rapprochement between genders in sexuality. These findings are relevant for researchers and practitioners, as they suggest the importance of considering contextual factors when developing effective interventions that aim to support adults with disabilities to live their sexuality.